PENDAMPINGAN IDENTIFIKASI UNIQUE SELLING POINT SEBAGAI STRATEGI DALAM PENGEMBANGAN PARIWISATA BERKELANJUTAN DESA TEGAL BALONG, BIMOMARTANI, NGEMPLAK, SLEMAN - Fransisca Desiana; Maria Angela Diva; Ferrynela Purbo Laksono (Universitas Sanata Dharma, 2022)
The issue of sustainable tourism development has now become a strategy that is widely applied in several countries. The sustainable aspect in question does not only look at the profit side but also the socio-cultural aspect. To be able to advance a tourist attraction, it is necessary to identify a Unique Selling Point (USP) so that it is more focused in every aspect of a sustainable tourism development strategy. Tegal Balong Village, Bimomartani, Ngemplak, Sleman is one of the villages in the Special Region of Yogyakarta which has extraordinary natural potential as a potential tourist attraction and other potentials. The problem faced by the village so far is the lack of a mechanism to determine the development of their tourism potential. The purpose of this service is to help Tegal Balong Village, Bimomartani, Ngemplak, Sleman find the identification of Unique Selling Point (USP) so that they are able to carry out their sustainable tourism development strategy. The implementation method is carried out by observation, field review, FGD, potential mapping, and proposed USP recommendations. As a result, there are several strengths and weaknesses of the village that should be addressed. Village potential is very abundant, especially natural potential, social entrepreneurship potential, cultural potential, and other potentials. USP recommendations can be used for the development of tourism packages and subsequent sustainable tourism development strategies.